2015
DOI: 10.1186/s40200-015-0186-6
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D & its analogues in type 2 diabetic nephropathy: a systematic review

Abstract: Nephropathy is one of the major complications of diabetes often leading to chronic kidney disease (CKD). Inflammation and oxidative stress are associated with pathogenesis of diabetic nephropathy (DN) and found to be regulated by nuclear receptors such as vitamin D receptors (VDR). Vitamin D and its analogues have been effectively used in patients with CKD. The review attempts to summarize the available evidence on the role of vitamin D in DN. Electronic databases (MEDLINE, EMBASE, and Cochrane Library) were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 41 publications
4
37
0
Order By: Relevance
“…As already mentioned, VD is linked to renin-angiotensin aldosterone system suppression, renal protection, antiproteinuric effects, improved diabetes control, and reduced cancer risk. Pleiotropic effects were detected in CKD patients too-treatment with VD and vitamin D analogs in patients with renal disease led to reduced proteinuria; similar findings were reported in patients with diabetic nephropathy with a relatively low risk for hypercalcemia [51,52]. However, the studies dealing with CKD patients are relatively few, compared to those reporting VD pleiotropy in the general population.…”
Section: Pleiotropic Effects In Ckd Patientssupporting
confidence: 52%
“…As already mentioned, VD is linked to renin-angiotensin aldosterone system suppression, renal protection, antiproteinuric effects, improved diabetes control, and reduced cancer risk. Pleiotropic effects were detected in CKD patients too-treatment with VD and vitamin D analogs in patients with renal disease led to reduced proteinuria; similar findings were reported in patients with diabetic nephropathy with a relatively low risk for hypercalcemia [51,52]. However, the studies dealing with CKD patients are relatively few, compared to those reporting VD pleiotropy in the general population.…”
Section: Pleiotropic Effects In Ckd Patientssupporting
confidence: 52%
“…It has been well documented that 1, 25(OH) 2 D 3 mediates the VDR’s biological effects by binding to it and then recruiting cofactors to form a transcriptional complex that binds to vitamin D response elements (VDRE) in the promoter region of target genes to alter transcriptional events within the target cells [8, 9]. Recent studies have shown that VDR-mediated signal transduction pathways play a critical role in the development of DN, such as inflammatory response [10], immune regulation, reduction of proteinuria, inhibition of the Ras system [9, 11], and prevention of fibrosis [12]. VDR can prevent the progression of diabetes by promoting islet cell repair and reducing insulin resistance and glucose tolerance(13).…”
Section: Introductionmentioning
confidence: 99%
“…Paricalcitol (19-nor-1, 25-hydroxy-vitamin D2), a synthetic vitamin D analog, can reduce urinary albumin in type 2 DM patients [9, 13-15]. As a vitamin D receptor agonist, it has been used for the treatment of hyperparathyroidism.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been shown that AGE-BSA activates proinflammatory pathways in other cell systems [22,23,24]. Although clinical studies have suggested that paricalcitol may have advantages over ‘classical' vitamin D3 [25,26], in our in vitro study, vitamin D3 and paricalcitol were equally effective in suppressing the NFκB activation (albeit in some experiments, e.g. retention of the p65 subunit in the cytoplasm, vitamin D3 was even more effective, whereas in other experiments, paricalcitol appears to work better than vitamin D3).…”
Section: Discussionmentioning
confidence: 99%